Comparison of Rigid Gas Permeable and Toric Soft Lens for Correcting Astigmatism - Ardiella Yunard; Tri Rahayu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To compare visual acuity correction of astigmatism and comfort between toric softcontact lens and rigid gas permeable. Thus, ophthalmologists will less reluctantly propose contactlenses for the patients with astigmatism, and maximize the potential advantages of contact lenses forthe wearer.Methods: Literature review of all prospective and retrospective studies which reported managementof astigmatism with rigid gas permeable of toric soft contact lenses. The articles were divided intocharacteristics and outcomes. Outcomes reviewd were visual acuity, lens fit characteristics, cornealstaining, and subjective problems.Results: Lens corrected visual acuity by toric soft lens showed variation, which 3 studies reported afew amount of visual loss from spectacles corrected. Meanwhile other studies reported better toric softlens corrected visual acuity than spectacles. In RGP group, four studies reported better or the samevisual acuity with spectacles, and only one study showed a few amount of visual loss. Visual clarityand poor comfort were the most frequent subjective problems in toric soft lens group. Meanwhile,dryness and poor comfort were the most frequent subjective problems in RGP group.Conclusion: RGP is superior than toric soft lens in correcting astigmatism. Meanwhile, toric soft lensprovides quick adaptation and comfort.Â Keywords: astigmatism, rigid gas permeable, toric soft lens